3T MRI improves the detection of transmantle sign in type 2 focal cortical dysplasia. Issue 1 (15th November 2013) - Mellerio, Charles; Labeyrie, Marc‐Antoine; Chassoux, Francine; Roca, Pauline; Alami, Odile; Plat, Monique; Naggara, Olivier; Devaux, Bertrand; Meder, Jean‐François; Oppenheim, Catherine
Summary Purpose Type 2 focal cortical dysplasia (FCD2) is one of the main causes of refractory partial epilepsy, but often remains overlooked by MRI. This study aimed to elucidate whether 3T MRI offers better detection and characterization of FCD2 than 1.5T, using similar coils and acquisition time. Methods Two independent readers reviewed the 1.5T and 3T MR images of 25 patients with histologically proven FCD2. For both magnetic fields, the ability to detect a lesion was analyzed. We compared the identification of each of the five criteria typical of FCD2 (cortical thickening, blurring, cortical signal changes, subcortical signal changes, and "transmantle" sign) and artifacts, using a four‐point scale (0–3). Interobserver reliability for lesion detection was calculated. Key Findings Seventeen lesions (68%) were detected at 3T, two of which were overlooked at 1.5T. Interobserver reliability was better at 3T (κ = 1) than at 1.5T (κ = 0.83). The transmantle sign was more clearly identified at 3T than 1.5T (mean visualization score: 1.72 vs. 0.56; p = 0.002). Significance The use of 3T MRI in patients suspected of type 2 FCD improves the detection rate and the lesion characterization owing to the transmantle sign being more clearly seen at 3T. This point is of interest, since this feature is considered as an MR signature of FCD2.